STRATEGIC CHANGE IN THE TURNAROUND PROCESS: THEORY AND EMPIRICAL EVIDENCE - BARKER III, VINCENT L.; DUHAIME, IRENE M. (Strategic Management Journal, 1997)
Early corporate turnaround theorists argued that strategic reorientations are central to the recovery process at many declining firms. However, subsequent large-sample empirical studies have reported that performance turnarounds for declining firms are primarily associated with cutback actions that increase efficiency, thus creating a gap between theory and empirical findings. We close this gap by presenting and empirically supporting a model proposing that the extent of strategic change initiated in a successful turnaround varies systematically with a declining firm’s need and capacity to reorient its strategy. Based on our model, we offer explanations for why past large-sample researchers were not able to verify the role of strategic change in the turnaround process and we reassert the adaptive role that strategic reorientations have in the turnaround attempts of declining firms with weak strategic positions. © 1997 by John Wiley & Sons, Ltd.